MEKANISME PENYELESAIAN SENGKETA HAK ATAS TANAH ADAT DAN PERLINDUNGAN HUKUM HAK ULAYAT MASYARAKAT ADAT SUKU MOI DI KABUPATEN SORONG - Semuel, Moldi; Wileys Sutikno, Aldilla Yulia; Kusmiadi, Moh Ery (Equality Before The Law, 2022)
Indigenous peoples group is a permanent and regular territorial unit in which the individuals are not only bound to the place of residence in a particular area, but are also bound to kinship ties in blood ties or the possibility of the same family relationship from one ancestor, either indirectly due to ties marriage or conventional ties (genealogy). land that has a very high economic value so that it is obliged to maintain and maintain its existence as an asset with economic value. The Moi tribe has rights over their land as a cultural heritage that can be used according to custom. The problem is how the mechanism for the settlement of disputes over customary land rights and the legal protection of customary rights of the indigenous people of the Moi tribe in Sorong district, the research method used is qualitative research, research techniques that produce descriptive data in the form of written or spoken words can be observed from people's behavior. Based on the results of the research, it can be seen that the customary dispute resolution mechanism can be carried out in two ways, namely Litigation and Non- litigation (Negotiation, Mediation and Customary Courts) and legal protection of the customary rights of the Moi tribe customary rights regulated in the 1945 Constitution to the applicable laws and regulations Law No. 21 of 2001 concerning Special Autonomy for Papua and Regional Regulation of Sorong Regency No. 10 of 2017 concerning Recognition and Protection of the Moi Tribe Traditional Law Community, Sorong Regency.